O medo bate à porta: Uma análise do percurso socioespacial do medo na literatura de horror - Perini, Alice da Rocha (2020)
This thesis intends to investigate how fear moves from one place to another in horror literature. The main idea is that, until the 1960 s, fear was not able to trespass house doors. In 1967, Ira Levin opens those doors in Rosemary s Baby. The Cold War at